Menuju UMKM Bankable: Simulasi Penggunaan SiApik (Aplikasi BI) Untuk Pencatatan Keuangan Digital - Esti Saraswati; Lusi Yuliarti (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
This community service program was designed to address the lack of financial literacy and digital accounting practices among micro, small, and medium enterprises (MSMEs) in Patikraja District, Banyumas. The aim was to improve financial recording skills by introducing SIAPIK, a digital financial recording application developed by Bank Indonesia that is compatible with SAK EMKM. The method used was a participatory and applicative approach involving 25 participants who were members of ASPIKMAS. The stages included preparation, socialization, direct training and simulation using real transaction data, continued by mentoring, and evaluation through pre-test and post-test. The results showed a significant improvement in participants’ understanding and skills, with an average score increase of 32% between pre-test and post-test. All participants were able to record transactions, prepare profit and loss statements, and financial position reports using SIAPIK. The program concluded that participatory training with digital tools is effective in strengthening financial literacy and supports the readiness of MSMEs to become more bankable by producing credible financial reports.